The Child Sport Concussion Assessment Tool 5th Edition (Child SCAT5): Background and rationale. Issue 11 (26th April 2017) - Davis, Gavin A; Purcell, Laura; Schneider, Kathryn J; Yeates, Keith Owen; Gioia, Gerard A; Anderson, Vicki; Ellenbogen, Richard G; Echemendia, Ruben J; Makdissi, Michael; Sills, Allen; Iverson, Grant L; Dvořák, Jiří; et al.
Abstract : This article presents the Child Sport Concussion Assessment Tool 5th Edition (Child SCAT5). The Sport Concussion Assessment Tool was introduced in 2004, following the 2nd International Conference on Concussion in Sport in Prague, Czech Republic. Following the 4th International Consensus Conference, held in Zurich, Switzerland, in 2012, the SCAT 3rd edition (Child SCAT3) was developed for children aged between 5 and12 years. Research to date was reviewed and synthesised for the 5th International Consensus Conference on Concussion in Sport in Berlin, Germany, leading to the current revision of the test, the Child SCAT5. This article describes the development of the Child SCAT5.